2008
DOI: 10.1144/sp308.17
|View full text |Cite
|
Sign up to set email alerts
|

Kornerupine sensu stricto associated with mafic and ultramafic rocks in the Lützow-Holm Complex at Akarui Point, East Antarctica: what is the source of boron?

Abstract: Kornerupine, (A, Mg, Fe)(Al, Mg, Fe) 9 (Si, Al, B) 5 O 21 (OH, F), is known from only five mafic or ultramafic settings worldwide (of the .70 localities overall). We report a sixth occurrence from Akarui Point in the Lützow-Holm Complex, East Antarctica, where two ruby corundum (0.22-0.34 wt% Cr 2 O 3 )-plagioclase lenses are found at the same structural level as boudinaged ultrabasic rocks in hornblende gneiss and amphibolite. Ion microprobe analyses of kornerupine give 13-59 ppm Be, 181-302 ppm Li, and 5466-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 41 publications
2
23
1
Order By: Relevance
“…It is important to note that this change is accompanied by the discontinuous change in the phosphorus concentration in the garnet. The discontinuous increase in the phosphorus concentration in the garnet rim is often observed in hightemperature metamorphic rocks accompanying partial melting, and the correlation with the phosphate assemblage included in the garnet, as reported in this study, has actually been observed worldwide Hiroi, 1997;Hiroi et al, 1997;Yang and Rivers, 2002;Kawakami and Motoyoshi, 2004;Kawakami et al, 2008). However, the generalization of the phosphorus zoning correlated with the change in phosphate assemblage included in garnet cannot be easily carried out at the present stage because of the lack of the detailed case studies on this problem.…”
Section: Systematic Change Of Phosphate Inclusion Assemblage and Corrsupporting
confidence: 82%
See 1 more Smart Citation
“…It is important to note that this change is accompanied by the discontinuous change in the phosphorus concentration in the garnet. The discontinuous increase in the phosphorus concentration in the garnet rim is often observed in hightemperature metamorphic rocks accompanying partial melting, and the correlation with the phosphate assemblage included in the garnet, as reported in this study, has actually been observed worldwide Hiroi, 1997;Hiroi et al, 1997;Yang and Rivers, 2002;Kawakami and Motoyoshi, 2004;Kawakami et al, 2008). However, the generalization of the phosphorus zoning correlated with the change in phosphate assemblage included in garnet cannot be easily carried out at the present stage because of the lack of the detailed case studies on this problem.…”
Section: Systematic Change Of Phosphate Inclusion Assemblage and Corrsupporting
confidence: 82%
“…However, it is well known that some minor elements like phosphorus commonly preserve chemical zoning with a non -diffusive nature even in the high -temperature metamorphic rocks Spear and Kohn, 1996;Hiroi, 1997;Hiroi et al, 1997;Chernoff and Carlson, 1999;Yang and Rivers, 2002;Yoshimura et al, 2004). Their zoning pattern is best observed under X -ray elemental mapping and it is characterized by a drastic, discontinuous change in their concentration within garnet (for examples of such zoning, see Hiroi et al, 1997;Chernoff and Carlson, 1999;Yang and Rivers, 2002;Yoshimura et al, 2004;Kawakami et al, 2008). Zoning in minor elements that is not affected by the diffusion in garnet is important because it can represent the contemporaneous surface (cf., Chernoff and Carlson, 1999) and contain considerable information about the reaction history that the rock has experienced (Spear and Pyle, 2002) even if the major element zoning in garnet is obscured by the later diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…This is the same sample studied by Kawakami et al (2008) and Nakamura et al (2014). The matrix of this sample consists mainly of garnet (~10 mm), biotite, sil-limanite, plagioclase, K-feldspar, and quartz with minor ilmenite, rutile (~100-500 µm), apatite, zircon, monazite, and spinel.…”
Section: Sillimanite-biotite-garnet Gneiss From Akarui Point (Sample mentioning
confidence: 98%
“…1). Peak metamorphic P-T condition was previously estimated at 770-790°C/ 7.7-9.8 kbar by applying Grt-Bt geothermometers and Grt-Al 2 SiO 5 -Qtz-Pl (GASP) geobarometers to a Sil-Bt-Grt leucogneiss (Kawakami et al, 2008) (Fig. 2a).…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation